Pengaruh Penambahan Daging Buah Anggur (Vitis Vinivera L.) Terhadap Karakteristik Sari Buah Anggur Berbulir - Dwi Wikananta, I Made; Ayu Ekawati, I Gusti; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i03.p12, 2023)
This study aims to determine the effect of adding fruit flesh to the characteristics of grape juice drinks and knowing the addition pulpy grape juice that can produce grainy grape juice with the best characteristics.. The design method used Completely Randomized Design with one treatment factor, namely the treatment of the addition of concentration of pulp grape (5%, 10%, 15%, 20%, 25%). Each treatment was repeated as many as 3 replays so that 15 experimental units were obtained. The results showed that different treatment of grape meat affects the pH value, total sugar, total solids, vitamin C, antioxidant activity, total anthocyanins as well as sensory properties of color, aroma, taste and overall acceptance of characteristics of pulpy grape juice. The best characteristic of the pulpy grape juice is in the treatment of pulp grape 25% with a pH of 3,37, total sugar 42,57%, total solids 31,01%, vitamin C 6,64 mg/ml, antioxidant activity 90,21%, total anthocyanins 249,95 mg/L as well as sensory properties of color and aroma (hedonic) liked, taste (hedonics) very like, sour taste (scoring) as well as overall acceptance of liked.